PENGARUH REVIEW PELANGGAN DAN ACARA PEMASARAN TERHADAP KEPUASAN PELANGGAN DENGAN IMPULSE BUYING SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Shopee Di Kota Semarang) - Iftita Rizky Amelia; Mahfudz Mahfudz (Diponegoro Journal of Management, 2022)
This study aims to analyze how much influence customer reviews and marketing events have on customer satisfaction with impulse buying as an intervening variable for e-commerce Shopee customers in Semarang City. The population used in this study are customers who have transacted at e-commerce Shopee for more than two times in the last a year who are domiciled in the city of Semarang. The sample used was 120 respondents. The sampling technique used was purposive sampling. The data collection method used is a questionnaire. This research uses Structural Equation Modeling (SEM) analysis technique using AMOS 22.0 analysis tool. The results showed that customer reviews and marketing events had a positive and significant effect on customer satisfaction. In addition, customer reviews and marketing events also have a positive and significant effect on impulse buying.